Oropharynx cancer after sleep apnea surgery. Issue 4 (8th April 2022) - Shires, Courtney Brooke; Sebelik, Merry
Abstract: Surgery can treat sleep apnea. An elderly male underwent lingual/palatine tonsillectomy for OSA. He was then found to have T3N2 p16+ squamous cell carcinoma. He is receiving chemoradiation. Recognition of occult malignancy in tonsillectomy specimens may facilitate early diagnosis and treatment for patients following sleep apnea surgery. Abstract : We report a 73‐year‐old male who underwent palatine and lingual tonsillectomy for obstructive sleep apnea. A few months later, he was found to have advanced oropharynx cancer. It is likely that his cancer could have been discovered at an earlier stage if his oropharyngeal tissue had been sent for pathology evaluation at the time of his sleep apnea surgery.